Utilizing Virtual Humans as Campus Virtual Receptionists - Zikky, Moh.; Suhardiman, Marvel Natanael; Fathoni, Kholid (Informatics Department-Universitas Dr. Soetomo, 2023)
To imitate human-like behavior is one of the greatest feats a computer software could achieve. Computers can produce close-to-realism avatars with similar looks and behaviors in this modern era. One of the works that computer software could achieve now is conveying information in a place that a receptionist usually does. Therefore a computer software capable of that is called a Virtual Receptionist. This paper aims to explore the use of virtual humans as virtual receptionists and compare it to human receptionists to find both advantages and disadvantages. This research utilizes a virtual human model that imitates the behavior of a human receptionist. Its movements are based on real-life movements recorded with motion capture. It could also communicate with users by processing the voice input using speech-to-text technology recorded by a microphone. The recorded input will then be analyzed to determine whether it contains information stored in a database. The virtual human will then show the user the answer to their question accordingly. Utilizing virtual humans can make the process more interactive and exciting because of its futuristic feel. This way, campuses can have appealing introductory media and support campuses to be more open to the public in the future. However, the agent can only respond with prepared answers and not generate its own when necessary. Transcribed text will be analyzed for words that indicate the user's required information. In this case, the information would be the information of research laboratories in the post-graduate building of the EEPIS campus.